COMPARATIVE STUDY OF MULTI CRITERIA DECISION MAKING METHODS IN A CASE STUDY OF THE BEST EMPLOYEE DECISION SUPPORT SYSTEMS - Istini, Syalis Ibnih Melati; Ahmad Apandi; Rama Dian Syah (Asosiasi Dosen Muda Indonesia, 2024)
Selecting the best employees is an alternative for companies to maintain and improve the quality of employee work. Being best employee is a matter of pride for every employee, so this good thing will also have an impact on the company. Having employees with good quality will certainly improve the quality of the company itself. Making decisions for the best employees is a challenge for companies because its subjective nature makes the selection inaccurate, so an objective decision-making system is needed according to the criteria. The purpose of this study is to compare three multi-criteria decision-making methods (MCDM) namely AHP (Analysis Hierarchy Process), SAW (Simple Additive Weighting Model) and TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution). Based on comparative studies from several journals, the results of the accuracy levels obtained from different methods show that there are different results from several cases discussed in reference journals, this is due to differences in the number of criteria and alternatives used for analysis.